Wear-resistant non-stick pan, inner coating of wear-resistant non-stick pan and forming method of inner coating
By using the melting layer of NiAl-Cr3C2 composite material on the surface of the aluminum alloy substrate of the non-stick pan, the problem of poor wear resistance of the existing non-stick pan coating is solved, and higher wear resistance and scratch resistance are achieved, ensuring the stability and safety of the coating.
Patent Information
- Application Number
- CN202411899980.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The coating of existing non-stick pans has poor wear resistance and is easily scratched, resulting in failure of anti-stick effect, and may even cause the coating to fall off and enter the food, posing a safety hazard.
The melting process is used to form a moltening layer of NiAl-Cr3C2 composite material on the surface of the aluminum alloy substrate, which serves as the basis for the non-stick layer to improve the wear resistance and scratch resistance of the inner surface of the pot.
It significantly improves the wear resistance and scratch resistance of the non-stick pan, enhances the mechanical strength of the inner surface of the pan, and ensures the stability and safety of the coating.
Smart Images

Figure CN119710519A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of non-stick coatings, and in particular relates to a wear-resistant non-stick pan, an inner coating thereof and a forming method thereof. Background Art
[0002] A non-stick pan is a pan with one or more layers of special materials on the inner surface to form a non-stick coating, which makes it difficult for food to adhere to it during cooking. This special material usually refers to polytetrafluoroethylene (PTFE), also known as Teflon, or a ceramic coating.
[0003] However, the wear resistance of the existing non-stick coatings needs to be improved, and the coatings are easily scratched. Once scratched or damaged, the coatings will not be able to achieve the anti-stick effect, and the detached coatings may even be mixed into food and ingested by the human body, posing a danger. Summary of the invention
[0004] The present invention aims to provide a wear-resistant non-stick pan, an inner coating and a forming method thereof, which solve the problems of poor wear resistance and easy scratching of the coating of the non-stick pan in the prior art.
[0005] The first aspect of the present invention provides an inner coating of a wear-resistant non-stick pan, which adopts the following technical solution:
[0006] The invention discloses an inner coating of a wear-resistant non-stick pan, comprising a sprayed layer formed on the surface of a substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the substrate is an aluminum alloy and the sprayed layer is composed of a NiAl-Cr3C2 composite material.
[0007] In the above scheme, aluminum alloy is used as the substrate. Before the non-stick layer is formed, a sprayed layer is formed on the surface of the substrate by a spraying process, which can assist the non-stick layer on the surface and improve the wear resistance of the non-stick pan.
[0008] The present invention screens the composition of the sprayed layer and selects the composition of the sprayed layer as a NiAl-Cr3C2 composite material. In the NiAl-Cr3C2 composite material, NiAl is the body of the sprayed layer, provides adhesion, and can also improve the anti-corrosion performance of the substrate aluminum alloy. Cr3C2 is a hard dispersed phase, which is evenly distributed in the NiAl layer, and can greatly improve the wear resistance and scratch resistance of the inner surface of the pot under a high temperature environment. Moreover, the NiAl-Cr3C2 composite material can form a tighter connection with the aluminum alloy substrate, so that the wear resistance is further improved.
[0009] Preferably, the mass ratio of NiAl to Cr3C2 is (94-96):(4-6) per 100 parts.
[0010] Further preferably, the mass ratio of NiAl to Cr3C2 is 95:5 per 100 parts.
[0011] Preferably, the thickness of the sprayed layer is 50 μm to 200 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 110 μm, 120 μm, etc.
[0012] More preferably, the thickness of the sprayed layer is 80 μm to 120 μm.
[0013] Preferably, the roughness Ra of the sprayed layer is 2 μm to 7 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, or 7 μm.
[0014] More preferably, the roughness Ra of the sprayed layer is 3 μm to 5 μm.
[0015] Preferably, a wire drawing surface is formed on the surface of the substrate, and the sprayed layer is formed on the wire drawing surface.
[0016] Preferably, the drawing depth of the drawing surface is 20 μm to 30 μm.
[0017] Preferably, before forming the sprayed layer, a sand layer is formed on the surface of the substrate.
[0018] Preferably, the roughness of the surface of the sand layer is 3 μm to 10 μm.
[0019] A second aspect of the present invention provides a method for forming the inner coating, comprising the following steps:
[0020] S1. Pre-treatment: wire drawing, degreasing and degreasing of the inner tank workpiece in sequence;
[0021] S2. Forming a spraying layer: plasma spraying spraying material to form a spraying layer, the flame velocity is 100 to 800 m / s, and the particle velocity is 50 to 150 m / s;
[0022] S3. Post-processing: sandpaper polishing, cleaning, drying;
[0023] S4. Forming a non-stick coating: Electrostatically spraying a non-stick coating to form a non-stick coating.
[0024] A third aspect of the present invention provides a wear-resistant non-stick pan comprising the above-mentioned inner coating.
[0025] By implementing the above technical solution, the present invention has the following beneficial effects:
[0026] 1. The present invention arranges a spray layer on the surface of the aluminum alloy substrate of the non-stick pan through a spraying process, and the spray layer adopts a NiAl-Cr3C2 composite material. NiAl is the body of the spray layer, which provides adhesion and can also improve the anti-corrosion performance of the substrate aluminum alloy. Cr3C2 is a hard dispersed phase, which is evenly distributed in NiAl, and can greatly improve the wear resistance and scratch resistance of the inner surface of the pan under high temperature environment.
[0027] 2. The present invention also significantly improves the gravity impact resistance performance on the basis of further improving the wear resistance by optimizing the specific composition ratio of the NiAl-Cr3C2 composite material.
[0028] 3. The present invention also adjusts the thickness and stretching depth of the sprayed layer to jointly improve the wear resistance and scratch resistance of the inner coating of the non-stick pan.
[0029] 4. The sprayed layer of the present invention can also enhance the mechanical strength of the substrate itself, making it more durable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the structure of the functional coating provided by the present invention.
[0031] In the figure, 101 is a substrate, 102 is a thermal spraying layer, and 103 is a non-stick layer. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides an inner coating of a non-stick pan, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of a NiAl-Cr3C2 composite material, and the mass ratio of NiAl to Cr3C2 is 96:4.
[0035] The non-stick layer adopts a hard ceramic non-stick layer. The non-stick layer of this embodiment is specifically: 26% tetraethoxysilane, 20% nano silica sol, 8% silane coupling agent, 0.5% acetic acid, 0.5% silicon carbide whisker, 3% copper chrome black, and 42% deionized water.
[0036] The above-mentioned inner coating is formed by a method comprising the following steps:
[0037] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0038] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0039] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0040] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0041] Example 2
[0042] This embodiment provides an inner coating of a non-stick pan, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of a NiAl-Cr3C2 composite material, and the mass ratio of NiAl to Cr3C2 is 95:5.
[0043] The non-stick layer adopts a hard ceramic non-stick layer. The non-stick layer of this embodiment is specifically: 26% tetraethoxysilane, 20% nano silica sol, 8% silane coupling agent, 0.5% acetic acid, 0.5% silicon carbide whisker, 3% copper chrome black, and 42% deionized water.
[0044] The above-mentioned inner coating is formed by a method comprising the following steps:
[0045] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0046] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0047] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0048] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0049] Example 3
[0050] This embodiment provides an inner coating of a non-stick pan, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of a NiAl-Cr3C2 composite material, and the mass ratio of NiAl to Cr3C2 is 94:6.
[0051] The non-stick layer adopts a hard ceramic non-stick layer. The non-stick layer of this embodiment is specifically: 26% tetraethoxysilane, 20% nano silica sol, 8% silane coupling agent, 0.5% acetic acid, 0.5% silicon carbide whisker, 3% copper chrome black, and 42% deionized water.
[0052] The above-mentioned inner coating is formed by a method comprising the following steps:
[0053] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0054] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0055] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0056] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that the mass ratio of NiAl to Cr3C2 is 100:0.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that the mass ratio of NiAl to Cr3C2 is 99:1.
[0061] Comparative Example 3
[0062] The difference from Example 1 is that the mass ratio of NiAl to Cr3C2 is 98:2.
[0063] Comparative Example 4
[0064] The difference from Example 1 is that the mass ratio of NiAl to Cr3C2 is 92:8.
[0065] Comparative Example 5
[0066] The difference from Example 1 is that the mass ratio of NiAl to Cr3C2 is 93:7.
[0067] The difference between Examples 1-3 and Comparative Examples 1-5 is that the mass ratios of NiAl and Cr3C2 are different.
[0068] In order to verify the influence of the mass ratio of NiAl to Cr3C2 on the performance of non-stick pans, the wear resistance and gravity impact resistance of non-stick pans formed with the inner coating corresponding to Examples 1 to 3 were tested. The test method and results are as follows.
[0069] Wear test: Use a 3M 7447C industrial scouring pad with water to wipe the coating of the specimen with a force of 10N. One round trip is counted as one time. If abrasion marks with a width of more than 1mm on the exposed substrate appear on the surface or 10 linear abrasion marks with a length of more than 2mm expose the substrate, the test is stopped.
[0070] Gravity impact resistance: A steel ball with a diameter of 30 mm falls freely from a set height and hits the front of the coating. Record the height and observe the coating surface. Adjust the height and test new samples until the coating cracks or falls off, then stop the test.
[0071] Table 1 Non-stick pan related performance test results corresponding to Examples 1-3
[0072] Internal coating Wear times Gravity impact resistance test Example 1 13w 2m Example 2 16w 1.8m Example 3 20w 1.5m Comparative Example 1 6w 2m Comparative Example 2 7w 1.7m Comparative Example 3 7w 1.6m Comparative Example 4 20w 1.1m Comparative Example 5 20w 0.9m
[0073] From the results shown in Table 1, when the mass ratio of NiAl to Cr3C2 is 96:4, 95:5, and 94:6, the wear resistance and gravity impact resistance are good. When the content of Cr3C2 is low, its wear resistance decreases significantly. When the content of Cr3C2 is high, although the wear resistance is improved, the brittleness of the material becomes larger, the impact resistance decreases, and the gravity impact resistance decreases significantly. Therefore, the mass ratio of NiAl to Cr3C2 is optimized to 94-96:4-6, that is, in the NiAl-Cr3C2 composite material, NiAl accounts for 94-96% and Cr3C2 accounts for 4-6%.
[0074] Example 4
[0075] This embodiment provides an inner coating of a wear-resistant non-stick pan, and based on the embodiment 1, a sandblasting step is added. The rest is the same as the embodiment 1.
[0076] The above-mentioned inner coating is formed by a method comprising the following steps:
[0077] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0078] S2. Sandblasting: After pre-treatment, the substrate surface is sandblasted with 30# white corundum sharp-angle sand to make the inner surface roughness of the pot blank reach Ra 5μm;
[0079] S3. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0080] S4. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0081] S5. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0082] After testing, the wear resistance reached 15w and the gravity impact resistance test reached 2m.
[0083] Example 5
[0084] The present embodiment provides an inner coating of a wear-resistant non-stick pan. On the basis of Embodiments 1-3, the mass ratio of NiAl to Cr3C2 is optimized to 95:5 for further optimization, and the thickness of the sprayed layer is adjusted (other things are the same as Embodiment 2), and the thickness of the sprayed layer is designed to be 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, and 200μm, respectively.
[0085] In order to verify the effect of the thickness of the sprayed layer on the performance of the non-stick pan, the wear resistance and gravity impact resistance of the non-stick pans with different thicknesses of the sprayed layer were tested. The test results are as follows.
[0086] Table 2 Test results of non-stick pan related properties corresponding to different thicknesses of sprayed layers
[0087] Spraying layer thickness Wear times Gravity impact resistance test 60μm 16 1.9 80μm 17 2.0 100μm 18 2.2 120μm 22 2.4 140μm 23 2.2 160μm 23 2.2 180μm 23 2.0 200μm 23 2.0
[0088] From the results shown in Table 2, the thickness of the sprayed layer has a certain influence on the results. Within a certain range, the overall trend is that with the increase of thickness, the wear resistance and gravity resistance are improved, but when the thickness reaches more than 140μm, the wear resistance does not continue to improve, and the gravity impact resistance does not improve, and even decreases. Considering the process, cost and performance of the non-stick pan, the thickness of the optimized sprayed layer is 80μm to 120μm.
[0089] Example 6
[0090] The present embodiment provides an inner coating of a wear-resistant non-stick pan. On the basis of Example 4, the thickness of the sprayed layer is selected to be 100 μm for further optimization, and an experiment is conducted on the effect of the roughness Ra of the sprayed layer on the performance of the non-stick pan (except for the thickness and roughness of the sprayed layer, everything else is the same as Example 2), and the roughness Ra of the sprayed layer is designed to be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, and 7 μm, respectively.
[0091] In order to verify the effect of the roughness of the sprayed layer on the performance of the non-stick pan, the wear resistance and gravity impact resistance of the non-stick pans with inner coatings corresponding to the sprayed layers with different roughness were tested. The test results are as follows.
[0092] Table 3 Test results of non-stick pan related properties corresponding to the sprayed layers with different roughness
[0093] Roughness of sprayed layer Wear times Gravity impact resistance test 2μm 20 1.5 3μm 22 2.0 4μm 26 2.7 5μm 18 2.2 6μm 18 1.6 7μm 14 1.5
[0094] From the results shown in Table 3, the roughness of the sprayed layer also has a certain influence on the performance of the non-stick pan. Within a certain range (2μm to 4μm), the overall trend is that with the increase of roughness, the wear resistance and gravity resistance are improved, but when the roughness is above 5μm, the wear resistance and gravity impact resistance are reduced. Considering the process, cost and the performance of the non-stick pan, the roughness of the sprayed layer is optimized to be 3μm to 5μm.
Claims
1. An inner coating of a wear-resistant non-stick pan, characterized in that: The invention comprises a sprayed layer (102) formed on the surface of a substrate (101) by a spraying process and a non-stick layer (103) formed on the surface of the sprayed layer (102), wherein the substrate (101) is an aluminum alloy and the sprayed layer (102) is composed of a NiAl-Cr3C2 composite material.
2. The inner coating of a wear-resistant non-stick pan according to claim 1, characterized in that: The mass ratio of NiAl to Cr3C2 is (94-96):(4-6) per 100 parts.
3. The inner coating of a wear-resistant non-stick pan according to claim 2, characterized in that: The mass ratio of NiAl to Cr3C2 is 95:5 per 100 parts.
4. The inner coating of a wear-resistant non-stick pan according to claim 1, 2 or 3, characterized in that: The thickness of the sprayed layer (102) is 50 μm to 200 μm.
5. The inner coating of a wear-resistant non-stick pan according to claim 1, 2 or 3, characterized in that: The roughness Ra of the sprayed layer (102) is 2 μm to 7 μm.
6. The inner coating of a wear-resistant non-stick pan according to claim 1, characterized in that: A wire drawing surface is formed on the surface of the substrate (101), and the sprayed layer (102) is formed on the wire drawing surface.
7. The inner coating of a wear-resistant non-stick pan according to claim 6, characterized in that: The drawing depth of the drawing surface is 30 μm to 100 μm.
8. The inner coating of a wear-resistant non-stick pan according to claim 1, characterized in that: It also includes a sand layer formed on the surface of the substrate (101) before forming the spraying layer.
9. The inner coating of a wear-resistant non-stick pan according to claim 8, characterized in that: The roughness of the surface of the sand layer is 3 μm to 10 μm.
10. The method for forming an inner coating of a wear-resistant non-stick pan according to any one of claims 1 to 9, characterized in that: The steps include: S1. Pre-treatment: Degreasing and degreasing of the aluminum alloy substrate formed by stamping and riveting; S2. Spraying: Plasma spraying spraying material to form a spraying layer, the flame velocity is 100-800m / s, and the particle velocity is 20-500m / s; S3. Post-processing: sandpaper polishing, cleaning, drying; S4. Spraying: Electrostatically spray the non-stick coating to form a non-stick coating.
11. A wear-resistant non-stick pan, characterized in that: The invention relates to an inner coating of a wear-resistant non-stick pan comprising the inner coating of any one of claims 1 to 9.